Establishment of a minimally invasive distal traumatic optic neuropathy model in mice to investigate cascade reactions of retinal glial cells. Issue 1 (5th December 2022) - Shen, Bingqiao; Yu, Huan; Zhang, Mingui; Chen, Junjue; Zhang, Yang; Xu, Shushu; Han, Ruiqi; Huang, Shouyue; Huang, Ping; Zhong, Yisheng
Abstract: Traumatic optic neuropathy (TON) is a complication of craniocerebral, orbital and facial injuries, leading to irreversible vision loss. At present, there is no reliable, widely used animal model, although it has been confirmed that TON can cause the loss of retinal ganglion cells (RGC). However, the cascade reaction of retinal glial cells underlying TON is unclear. Therefore, the establishment of an animal model to explore the pathological mechanism of TON would be of great interest to the scientific community. In this study, we propose a novel mouse model utilizing a 3D stereotaxic apparatus combined with a 27G needle to evaluate damage to the optic nerve by micro‐CT, anatomy, SD‐OCT and F‐VEP. Immunofluorescence, western blotting, qPCR experiments were conducted to investigate the loss of RGCs and activation or inactivation of microglia, astrocytes and Müller glial cells in the retina from the first week to the fourth week after modeling. The results showed that this minimally invasive method caused damage to the distal optic nerve and loss of RGC after optic nerve injury. Microglia cells were found to be activated from the first week to the third week; however, they were inactivated at the fourth week; astrocytes were activated at the second week of injury, while Müller glial cells were gradually inactivated following injury. In conclusion, this method can be used as a novel animal model of distal TON, that results in a series of cascade reactions of retinal glial cells, which will provide a basis for future studies aimed at exploring the mechanism of TON and the search for effective treatment methods.